2013
DOI: 10.1016/j.yfrne.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of body temperature and LH secretion by hypothalamic KNDy (kisspeptin, neurokinin B and dynorphin) neurons: A novel hypothesis on the mechanism of hot flushes

Abstract: Despite affecting millions of individuals, the etiology of hot flushes remains unknown. Here we review the physiology of hot flushes, CNS pathways regulating heat-dissipation effectors, and effects of estrogen on thermoregulation in animal models. Based on the marked changes in hypothalamic kisspeptin, neurokinin B and dynorphin (KNDy) neurons in postmenopausal women, we hypothesize that KNDy neurons play a role in the mechanism of flushes. In the rat, KNDy neurons project to preoptic thermoregulatory areas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
191
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(216 citation statements)
references
References 193 publications
5
191
0
8
Order By: Relevance
“…Rapid estrogen withdrawal appears to mediate flushes in women via an increase in release of neurokinin B, and possibly other mediators, from the hypothalamus (Jayasena et al 2015). Neurokinin B acts on neurokinin 3 receptors in the hypothalamic median preoptic nucleus, to stimulate heat dissipation effectors such as cutaneous vasodilatation, diaphoresis and coldseeking behaviour (Rance et al 2013, Jayasena et al 2015. In perimenopausal and postmenopausal women, estrogen replacement is the most effective pharmaceutical strategy for mitigating hot flushes (Nelson 2004), although an oral neurokinin 3 receptor antagonist recently appears promising (Prague et al 2017).…”
Section: Effect Of Estradiol On Vasomotor Symptomsmentioning
confidence: 99%
“…Rapid estrogen withdrawal appears to mediate flushes in women via an increase in release of neurokinin B, and possibly other mediators, from the hypothalamus (Jayasena et al 2015). Neurokinin B acts on neurokinin 3 receptors in the hypothalamic median preoptic nucleus, to stimulate heat dissipation effectors such as cutaneous vasodilatation, diaphoresis and coldseeking behaviour (Rance et al 2013, Jayasena et al 2015. In perimenopausal and postmenopausal women, estrogen replacement is the most effective pharmaceutical strategy for mitigating hot flushes (Nelson 2004), although an oral neurokinin 3 receptor antagonist recently appears promising (Prague et al 2017).…”
Section: Effect Of Estradiol On Vasomotor Symptomsmentioning
confidence: 99%
“…Post-menopausal women have been shown to demonstrate hypertrophy of these neurons in the hypothalamic arcuate nucleus, changes that have also been demonstrated in young monkeys after ovariectomy and reversed by oestrogen replacement (15). Animal models have studied the connections between KNDy neurons and the pathways that control heat-defence effectors involving the preoptic structures (16) and have also evaluated the thermoregulatory effects of ablating KNDy neurons, indicating that KNDy neurons facilitate cutaneous vasodilatation, an important heat dissipation effector (17). Based on these previous investigations, Prage et al very recently reported a randomised doubleblind placebo-controlled trial, using an oral neurokinin 3 receptor antagonist (MLE4901).…”
Section: Neural Mechanism: Wet Flushingmentioning
confidence: 99%
“…In a recent randomised trial researchers found that NKB antagonist (AZD4901) administration in patients having PCOS resulted in reduced LH pulse frequency and secretion with subsequent remarkable and sustained reduction in testosterone levels [183]. Likewise, kisspeptin and NKB antagonists might be helpful in treating patients having precocious puberty [1] with the additional benefit of reduced menopausal side effects [184][185][186].…”
Section: Clinical Utility Of Kisspeptins In Reproductionmentioning
confidence: 99%